Transcription factor-7-like 2 gene variants are strongly associated with type 2 diabetes in Lebanese subjects - Nemr, Rita (2012)
We tested the association of TCF7L2 variants with type 2 diabetes (T2DM) in 691 Lebanese people and 919 controls. rs7901695, rs4506565, rs7903146, rs12243326, rs7895340, and rs12255372 minor allele frequencies were higher in T2DM. Haplotype analysis (rs7901695–rs4506565–rs7903146–rs12243326–rs7895340–rs11196205–rs12255372) identified positively- (2122112, 2222222) and negatively- (1111111) T2DM-associated haplotypes. TCF7L2 is a common T2DM candidate gene in Lebanese people.